Estudo de Matérias-Primas do Rio Grande do Norte para Uso em Revestimento Poroso: Influência do teor de dolomita e temperatura de calcinação nas propriedades físico-mecânicas - Silva Neto, Gilson da (2007)
The state of Rio Grande do Norte presents a great potentiality for the production of ceramic tiles because of having natural raw material in quantity and quality making its economical exploration possible, beyond the great energetic differential of the state, the natural gás. This works aims to study the influence of the dolomite and granulometry concentration and calcinations temperature in the obtaining of formulations for porous coverings which have to be coherent to the project,s specifications. The experiments have involved the physical-chemical and mineralogical characterizations of raw materials and mechanical tests in the dry and burnt proof bodies preceding a mixture experiment planning with the use of the response surface methodology, in order to get the best raw materials combinations to produce a ceramic mass with specific properties. The twelve ceramic masses studied in this work were prepared by the via dry process, characterized, shaped by uniaxial pressing and sinterized in the temperatures of 940ºC, 1000ºC, 1060ºC, 1120ºC and 1180ºC, using a fast burning cycle. The crystalline phases formed during the sintering in the temperatures in study have revealed the presence of anorthite and diopside beyond quartz with a remaining phase. These phases were the main responsible ones by the physical- mechanical properties of the sinterized proof bodies. The proof bodies after the sintering stage have presented water absorption higher than 10% and a good dimensional stability in all studied temperatures. However, the flexural breaking strength results in the temperatures of 940ºC, 1000ºC and 1060ºC, under the temperature zone of the vitrification of ceramic whiteware do not reach the flexural breaking strength specific for the porous wall tile (15 MPa), but in the temperature of 1120ºC next to the vitrification temperature zone, some whiteware ceramic (formulations) has reached the specified value for the porous wall tile. The results of this work have showed that the studied raw materials have great importance for used in the production of porous wall tiles (BIII)